Applying Ice Cream Stick Media To Improve Grade Eight Students’ Ability In Reading Comprehension Of Descriptive Text At SMP Negeri 2 Pematang Siantar - Reulina Arita Barus; David Berthony Manalu; Christian Neni Purba (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The research aims to find out the effect of Ice Cream Stick Media to improve students’ ability in reading comprehension of descriptive text at SMP Negeri 2 Pematang Siantar. This research is quantitative research with quasi experimental research design, according to Ary, et al (2010:426) quantitative research is research that gathers numeric data through control procedures and analyses to answer predetermined questions or test hypothesis. The population is the grade eight of SMP Negeri 2 Pematang Siantar with a total of 344 students. The sample of this research is divided into two classes namely experimental class (VIII-7) consist of 30 students that use Ice Cream Stick Media and control class (VIII-6) consist of 30 students that use conventional strategy. The data collection instrument uses a multiple choice for pre-test and post-test. The research finds that the mean of post-test in experimental class is 73.1 and the mean of post-test in control class is 65. After that the researcher find that the ttest is higher than ttable (2.066 > 1.672) at the level significance is 5%. Based on the result finding Ha is accepted and Ho is rejected. Therefore, it can be concluded that use Ice Cream Stick Media significantly affects the students’ ability at SMP Negeri 2 Pematang Siantar in reading comprehension of descriptive text.